2014
DOI: 10.1021/ie500241b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ratio and Preparation Method on Nickel–Tungsten Carbide Catalyst for Hydrocracking of Distillers Dried Grains with Solubles Corn Oil

Abstract: The hydrocracking of distillers dried grains with solubles (DDGS) corn oil over bimetallic carbide catalysts was explored for green diesel production. A catalyst composed of nickel–tungsten (Ni–W) carbide supported on Al-SBA-15 was designed based on the ability of nickel to adsorb and activate hydrogen and the potential of tungsten for hydrogenation reactions. Four different Ni–W ratios (1:9, 1:1, 2:1, and 9:1) were prepared by the impregnation method to study the effect of metal ratio on the catalyst structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In a third paper [224] published by the same group a new NiWC/Al-SBA-15 catalyst series was studied for the hydrocracking of distillers dried grains with solubles (DDGS) corn oil (Table 6, entry 3).The effect of the Ni/W ratio and the catalyst preparation method on activity, selectivity, and durability of the catalyst for green diesel production was investigated under relatively mild reaction conditions. The metal dispersion on the support and the alloy formation were studied to elucidate their effects on the catalyst performance and provide a better understanding of the hydrocracking process.…”
Section: Development Of Bimetallic (Nimo Niw) Carbide Nitride and Pmentioning
confidence: 99%
“…In a third paper [224] published by the same group a new NiWC/Al-SBA-15 catalyst series was studied for the hydrocracking of distillers dried grains with solubles (DDGS) corn oil (Table 6, entry 3).The effect of the Ni/W ratio and the catalyst preparation method on activity, selectivity, and durability of the catalyst for green diesel production was investigated under relatively mild reaction conditions. The metal dispersion on the support and the alloy formation were studied to elucidate their effects on the catalyst performance and provide a better understanding of the hydrocracking process.…”
Section: Development Of Bimetallic (Nimo Niw) Carbide Nitride and Pmentioning
confidence: 99%
“…The mixture was filtered, dried, and calcined at 550 °C for 4 h. According to our previous work [8], the catalysts NiNb, NiMo, NiW, and NiZr were prepared in the ratio of 6.67 wt% Ni:3.33 wt% M (M = Nb, Mo, W, Zr) by the wet co-impregnation of aqueous solutions of (Ni(NO 3 ) 2 . Carburization was conducted using temperature-programmed reduction (TPR) according to the method of Claridge et al [42].…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The hydrocracking process is the most developed route for removal of oxygen from triglycerides and fatty acids to produce biofuels [5][6][7]. Our previous study [8] has shown that bimetallic carbide catalysts (NiWC/Al-SBA-15) prepared by a Dendrimer-Encapsulated-Nanoparticles (DENP) method with a Ni-W ratio of 2:1 led to a complete conversion of DDGS corn oil (>95% triglycerides) over 16 continuous days with 100% diesel selectivity for 4 days at 400 °C and 4.48 MPa. However, this process requires high pressure of H 2 and has issues related to catalyst deactivation due to the presence of water [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous work [17] Carburization was conducted using temperature-programmed reduction (TPR) according to the method of Claridge et al [22]. Each metal oxide precursor was placed in a quartz tube and subjected to a flow of 20% CH 4 /80% H 2 at 30 cm 3 /min and a heating rate of 10 K/min to 250 °C, followed by 2.0 K/min to 730 °C.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The conversion of soybean oil reached 100% and the selectivity for green diesel was 97% for the NiMo carbide catalyst over Al-SBA-15 during 7 days at 400 °C and 4.48 MPa. Our earlier study investigated the effect of catalyst preparation method and Ni-W ratio on the carbide form of the NiW/Al-SBA-15 catalyst activity and selectivity [17]. The catalyst prepared by Dendrimer-Encapsulated-Nanoparticles (DENP) method with a Ni-W ratio of 2:1 led to a complete conversion of DDGS corn oil for 16 days and 100% diesel selectivity for 4 days at 400 °C and 4.48 MPa.…”
Section: Introductionmentioning
confidence: 99%